PENJABARAN GOOD CORPORATE GOVERNANCE (GCG) DALAM PENGADAN BARANG DAN JASA PADA PLN BALI - Dwi Suarini, Luh Putu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 3 (2015), 2015)
Research in connection with the theme is “ Implementation of Good Corporate Governance (GCG) in Procurement at PLN Bali”. The problems are researched the translation of good corporate governace forms in the procurement of goods and services at PLN Bali and the form of the procurement of goods and services at PLN Bali. This research includes the category of empirical legal research, legal research is a empirical means reviewing the practical reality in daily life - today. The nature of the research is descriptive research that has a goal to paint a picture of something in the area and at a certain moment. Furthermore, the technique used is to study documents, interviews, Non- Probability Sampling, purposive sampling. Procurement of goods or services in PLN involves many parties, the employees who were appointed to take care of such procurement and future providers of goods and services. In this relationship unfair business competition or the price is too high or low in supply. However, the existence of e-procurement and the correct procedures in the procurement of goods and services as well as the concept of GCG which also animates the principles of procurement of goods and services. Procedures in the procurement of goods and services as well as the principles of GCG, the procurement in PLN can be carried out transparently, responsibly, independently, fairly and equitably.
Keywords: Good Corporate Governance; PLN; Procurement of goods; services